Pesona Mahar Unik: Studi Pemberian Mahar Saat Akad Nikah Di Kabupaten Merauke - Susanti, Ana; Faisal, Faisal; Yamin, Ade (LPPM UNU BLITAR, 2025)
This research is motivated by the emergence of unique dowry giving by several couples in Merauke Regency during the Marriage Agreement. Therefore, the purpose of this study is to see what unique dowry is like and the factors that affect it. And then the practice of giving this unique dowry will be analyzed using Islamic legal theory in order to get legal findings in the practice of giving this unique dowry. This research was carried out with a field study through an empirical approach where data was obtained using interviews, observations and documentation. The findings show that the giving of a unique dowry in Merauke Regency during the marriage ceremony is the amount of money given by the groom to be to the bride. Where the amount of dowry money given is adjusted to the date of birth of the bride and the date of marriage of the two brides. Furthermore, the second finding is that the factors behind the giving of the unique dowry are the trend of modernization and the influence of information technology so that the bride and groom in Merauke Regency follow the trend style and information of the dowry. Then there is also a factor of pride with the giving of the unique dowry of the two married couples. By looking at the form of dowry that is uniquely applied and the factors that make the unique dowry carried out, this practice according to Islamic law is not contrary and allowed.